The economic development of Kenya - International Bank for Reconstruction and Development (Baltimore: John Hopkins Press, 1963)
This is the report of an economic survey mission to Kenya which was organized by the International Bank for Reconstruction and development at the request of the Governments of Kenya and the United Kingdom. The task of the mission was to undertake a general review of the economic potential of Kenya and make recommendations to the Kenyan government.
Includes index
Includes bibliographies
usc 23/01/2019
Loans
Keywords: Economic history; Economic conditions; Kenya